A Review of Amelia Walker, Helen Grimmett, and Alison L. Black’s, Ludic Inquiries Into Power and Pedagogy in Higher Education: How Games Play Us - McDonough, Sharon (Art/Research International)

(untitled) (University of Alberta, 2026)
This narrative offering, interwoven with poetry, is my response to Walker, Grimmett, and Black’s (2024) edited volume Ludic Inquiries into Power and Pedagogy in Higher Education: How Games Play Us. In sharing this, I illustrate the way that I engaged with the book as a reader, how it resonated with me, and how it prompted me to think about my work in higher education and the nature of finite and infinite games, rules, and play. Throughout the review, I use “notes to self” in my narrative to highlight moments that connect with ideas in the book, as well as self-authored poetry, generated in response to concepts explored in the book. I also use the editors’ first names as a deliberate move to foster connection and conversation.